Comparative analysis of combinations of dimension reduction and data mining techniques for malware detection - JEFFREY, YIU (Archīum Ateneo, 2011)
Many malware detectors utilize data mining techniques as primary tools for pattern recognition. As malware continue to be produced at an increasing rate, so does the need more efficient and effective detectors. However, detection speed and accuracy are us